Perceptions of Relatives’ towards Medico-Legal Investigation and Forensic Autopsy: A Survey from Rural Haryana - Goel, Shelesh; Chikkara, Pankaj; Chhoker, Virender K; Singh, Abhishek; Bhardwaj, Anu; DR, Rajesh; Singh , Nand Kishore (Journal of Indian Academy of Forensic Medicine, 2015)
Currently a greater emphasis is being placed on the active participation of patients and their  families; it is time that the attitude and feelings of the families with regard to autopsies are investigated.  Therefore present study was planned with an objective to analyze deceased family member’s attitudes  towards medico-legal investigation and Forensic autopsy. An additional objective was to determine  factors influencing autopsy refusal by relatives of the deceased. 200 family members or relatives were  selected randomly from the list of address and contact number prepared from the autopsy cases from  2010 to 2012. Data of 165 was processed and analyzed. 30.9% of the respondents had a primary level of  education while 35.2% of them were illiterates. A high proportion of study subjects considered that  autopsy would result in visible disfigurement of the body. Involvement of police/ court (92.1%), no use in  knowing the cause of death/ nature of death (88.6%) and autopsy delays funeral (83.4%) were three top  most causes responsible for autopsy refusal by family members or relatives of the deceased. The  experience and opinions of relatives and family members can be utilized in more effective management of  medico-legal cases.
Keywords: Autopsy; Family members; Perceptions; Medico-legal